Mechanisms Involved in the Neuroprotection of Electroacupuncture Therapy for Ischemic Stroke - Xing, Ying; Zhang, Min; Li, Wen-Bin; Dong, Fang; Zhang, Feng (Frontiers in Neuroscience, 2018)
Stroke is one of the main causes of death all over the world. As the combination of acupuncture and electric stimulation, electroacupuncutre is a safe and effective therapy, which is commonly applied in ischemic stroke therapy in both experimental studies and clinic. The review was performed via searching the related articles in databases of OVID, PUBMED, and ISI Web of Science, from respective inception to May 2018. In this review, we summarized the mechanism of EA for ischemic stroke via a series of factors, consisting of apoptosis related factors, inflammatory factors, autophagy related factors, growth factors, transcriptional factors, cannabinoid CB1 receptors, and other factors. In summary, EA stimulation may effectively alleviate ischemic brain injury via a series of signal pathways and multiple factors.